High voltage lithium nickel manganese oxide based positive electrode material and its manufacturing method and application

JP2025505078AActive Publication Date: 2025-02-21ANHUI BOSHI HIGH-TECH NEW MATERIAL CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2024500472
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-01-13
Filing Date
2023-11-17
Publication Date
2025-02-21
Estimated Expiration
2043-11-17

AI Technical Summary

Benefits of technology

【0017】 従来技術と比較して、本発明では、粒径が50~800nmである小粒子の一次粒子からなるコアと粒径が1~5μmである大粒子の一次粒子からなる表層で形成されたコアシェル構造を有する高電圧のニッケルマンガン酸リチウム系正極材料を提供する。本発明で提供される正極材料は表層が大粒子の一次粒子であり内部が小粒子の一次粒子であるシェル-コア構造を持っている。表層の大粒子高密度構造によれば、ニッケルマンガン酸リチウム正極材料がロールプレスされた後に破砕されることがなく、材料内部への電解液の浸入によるマンガンの溶解を効果的に回避でき、したがって材料の圧実性能とサイクル性能が向上する。また、内部の小粒子構造によれば、リチウムイオン移動度および電気伝導率が高くなり、材料のレート性能の向上が図れる。また、本発明で提供される正極材料の製造方法は、プロセスが簡単で制御可能であり、環境に優しく、迅速かつ大規模の生産に有利であり、生産コストが低い。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025505078000001_ABST
    Figure 2025505078000001_ABST
Patent Text Reader

Abstract

The present invention provides a high-voltage lithium nickel manganese oxide-based positive electrode material having a core-shell structure formed of a core made of small primary particles having a particle size of 50 to 800 nm and a surface layer made of large primary particles having a particle size of 1 to 5 μm. The positive electrode material provided by the present invention has a shell-core structure in which the surface layer is made of large primary particles and the inside is made of small primary particles. Due to the large particle high-density structure of the surface layer, the lithium nickel manganese oxide positive electrode material is not crushed after roll pressing, and the dissolution of manganese due to the infiltration of the electrolyte into the material can be effectively avoided, thereby improving the pressing performance and cycle performance of the material. In addition, the small particle structure in the inside increases the lithium ion mobility and electrical conductivity, improving the rate performance of the material. In addition, the manufacturing method of the positive electrode material provided by the present invention is a simple and controllable process, is environmentally friendly, is advantageous for rapid and large-scale production, and has low production costs.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention belongs to the technical field of electrochemical energy storage, specifically relates to a high-voltage lithium nickel manganese oxide-based positive electrode material and its manufacturing method and application. This application claims priority to a Chinese patent application filed with the China Patent Office on January 13, 2023, application number 202310071138.X, with the invention title "High-voltage lithium nickel manganese oxide-based positive electrode material and its manufacturing method and application", the entire contents of which are incorporated herein by reference. [Background technology]

[0002] Lithium-ion batteries have the advantages of high discharge voltage, high energy density, and long cycle life, and are widely used in fields such as mobile phones, laptops, power tools, and electric vehicles. Compared with commercially available positive electrode materials, high-voltage lithium nickel manganese oxide has a discharge voltage of 4.7V and a theoretical specific capacity of 147mAh / g, and the energy density reaches 650Wh / kg, which can meet the needs of lithium-ion batteries with high energy density and high power output.

[0003] However, during charging and discharging, high-voltage lithium nickel manganese oxide is prone to side reactions with the electrolyte, which may cause a rapid drop in the discharge capacity of the battery. In order to reduce the dissolution of Mn by the electrolyte without directly contacting the electrode material with the electrolyte, a method called surface coating is available, which improves the cycle stability of lithium nickel manganese oxide.

[0004] Chinese Patent No. 105374997 describes a method for preparing lithium nickel manganese oxide coated with a composite material. The lithium nickel manganese oxide coated with a composite material is prepared by adding a composite solution of calcium salt, zirconium salt and titanium salt to a suspension of pure phase lithium nickel manganese oxide precursor to prepare a mixed solution in a certain ratio, and at the same time adding PEG as a dispersing agent, citric acid as a complexing agent, and ammonia water to adjust the pH, mechanically stirring, reacting in a constant temperature water bath, removing and aging, filtering, washing, drying, and removing CaO, ZrO, etc. 2 , TiO 2 The lithium nickel manganese oxide precursor was obtained by coating the precursor with ZnO, followed by calcination and annealing in an air atmosphere. However, during the roll pressing of the pole pieces, the surface structure of the material is loose, and the material particles may be crushed under the roll pressure, so that the coating layer is destroyed and peeled off from the surface of the material, which greatly reduces the cycle performance of the battery.

[0005] The core-shell structure can enhance the structural stability of the lithium nickel manganese oxide material and effectively avoid the material from being crushed by the roll pressure, so that the material's compression performance is improved. China Patent No. 105024064 describes a submicron-level yellow-shell structured lithium nickel manganese oxide and its preparation method. The lithium nickel manganese oxide positive electrode material is obtained by high-temperature sintering using lithium nitrate, nickel nitrate hexahydrate and self-produced manganese trioxide as raw materials. In addition, the size of the material particles and the size of the pores are adjusted according to the effect of the warming time on the size of the nano-agglomerated particles and the size of the pores. However, the lithium nickel manganese oxide material prepared by this method has a large specific surface area with a "shell" structure, and the "shell" is cracked and there is a gap between the "shell" and the "yellow", so that it is easily crushed when subjected to a large roll pressure, and has poor compression performance. Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention has been made in view of the above circumstances, and aims to provide a high-voltage lithium nickel manganese oxide-based positive electrode material and its manufacturing method and application. The high-voltage lithium nickel manganese oxide-based positive electrode material provided by the present invention does not break even after roll pressing, and has excellent pressing performance, cycle performance, and rate performance. [Means for solving the problem]

[0007] The present invention provides a high-voltage lithium nickel manganese oxide-based positive electrode material. The positive electrode material has a core-shell structure formed of a core made of small primary particles and a surface layer made of large primary particles. The large particles have a particle size of 1 to 5 μm, and the small particles have a particle size of 50 to 800 nm.

[0008] Preferably, the positive electrode material has a particle size of 6 to 15 μm, a core size of 1 to 10 μm, and a surface layer thickness of 3 to 5 μm.

[0009] Preferably, the positive electrode material has two charging stages, a charging stage I in the range of 4.6 to 4.74 V and a charging stage II in the range of 4.74 to 4.8 V. The voltage difference between charging stages I and II is 0.02 to 0.2 V, and the capacity ratio between charging stages I and II is 0.1 to 1:1.

[0010] The present invention also provides a method for producing a semiconductor device comprising the steps of: a step A of mixing a mixed solution of a nickel source compound and a manganese source compound, a solution of a crystal grain refiner, a complexing agent, and a precipitating agent, and carrying out a coprecipitation reaction to obtain a suspension I; a step B of mixing a mixed solution of a nickel source compound and a manganese source compound, a complexing agent, a precipitant, and the suspension I, and carrying out a coprecipitation reaction to obtain a suspension II; Step C of filtering, washing and drying the suspension II to obtain a lithium nickel manganese oxide precursor; and D. mixing the lithium nickel manganese oxide precursor with a lithium source compound and sintering the mixture to obtain a high-voltage lithium nickel manganese oxide-based positive electrode material.

[0011] Preferably, the nickel source compound is selected from the group consisting of nickel sulfate, nickel nitrate, nickel chloride, and combinations thereof; the manganese source compound is manganese sulfate or / and manganese chloride; The complexing agent is aqueous ammonia; The precipitating agent is a sodium hydroxide solution.

[0012] Preferably, the grain refiner is selected from the group consisting of niobium chloride, ammonium niobium oxalate, niobium fluoride, potassium hexafluoroniobate, molybdenum chloride, sodium molybdate, molybdenum oxalate, molybdenum fluoride, molybdenum sulfide dihydrate, and combinations thereof.

[0013] Preferably, in step A), the molar ratio of metal ions to the grain refiner in the mixed solution of the nickel source compound and the manganese source compound is 1:0.001-0.05.

[0014] Preferably, the molar ratio of the amount of the mixed solution of the nickel source compound and the manganese source compound in step A) to the amount of the mixed solution of the nickel source compound and the manganese source compound in step B) is 0.1 to 1:1.

[0015] Preferably, in step D), the lithium source compound is selected from the group consisting of lithium carbonate, lithium hydroxide, lithium chloride, lithium fluoride and combinations thereof. Preferably, the sintering is performed at a temperature of 750 to 950° C. for a time of 6 to 24 hours.

[0016] The present invention also provides a lithium-ion battery comprising the high voltage lithium nickel manganese oxide based positive electrode material. Effect of the Invention

[0017] Compared with the prior art, the present invention provides a high-voltage lithium nickel manganese oxide-based positive electrode material having a core-shell structure formed of a core made of small primary particles having a particle size of 50-800 nm and a surface layer made of large primary particles having a particle size of 1-5 μm. The positive electrode material provided by the present invention has a shell-core structure in which the surface layer is made of large primary particles and the inside is made of small primary particles. Due to the large particle high-density structure of the surface layer, the lithium nickel manganese oxide positive electrode material is not crushed after roll pressing, and the dissolution of manganese due to the infiltration of the electrolyte into the material can be effectively avoided, thus improving the pressing performance and cycle performance of the material. In addition, the small particle structure in the inside increases the lithium ion mobility and electrical conductivity, thereby improving the rate performance of the material. In addition, the manufacturing method of the positive electrode material provided by the present invention is simple and controllable, environmentally friendly, advantageous for rapid and large-scale production, and has low production costs. [Brief description of the drawings]

[0018] [Figure 1] FIG. 1 is an SEM image of the lithium nickel manganese oxide described in Example 1. [Diagram 2] FIG. 2 is an SEM image of a cross section of the lithium nickel manganese oxide described in Example 1. [Diagram 3] FIG. 3 is an SEM image of a cross section of the lithium nickel manganese oxide described in Comparative Example 1. [Figure 4] FIG. 4 is a comparison diagram of the charging curves of the batteries prepared in Example 1 and Comparative Example 1. [Diagram 5] FIG. 5 is a comparison diagram of the rate and cycle performance of the batteries produced in Example 1 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The present invention provides a high-voltage lithium nickel manganese oxide-based positive electrode material having a core-shell structure formed of a core made of small primary particles having a particle size of 50 to 800 nm and a surface layer made of large primary particles having a particle size of 1 to 5 μm.

[0020] The high voltage lithium nickel manganese oxide based positive electrode material provided by the present invention comprises a core consisting of small primary particles, wherein the small particles have a particle size of 50-800 nm, preferably 100-500 nm, and more preferably 200-300 nm.

[0021] The high voltage lithium nickel manganese oxide based positive electrode material provided by the present invention further comprises a surface layer covering the core, wherein the surface layer is formed from large primary particles having a particle size of 1 to 5 μm, preferably 1 to 3 μm, and more preferably 2 to 3 μm.

[0022] In the present invention, the positive electrode material has a particle size of 6 to 15 μm, preferably 8 to 12 μm, a core size of 1 to 10 μm, preferably 3 to 8 μm, more preferably 5 to 7 μm, and a surface layer thickness of 3 to 5 μm.

[0023] The positive electrode material has two charging stages, a charging stage I and a charging stage II. Here, the charging stage I is in the range of 4.6 to 4.74 V, preferably in the range of 4.62 to 4.74 V, and more preferably in the range of 4.65 to 4.72 V. The charging stage II is in the range of 4.74 to 4.8 V, preferably in the range of 4.74 to 4.79 V, and more preferably in the range of 4.75 to 4.78 V. The voltage difference between the charging stages I and II is 0.02 to 0.2 V, preferably 0.03 to 0.1 V, and more preferably 0.04 to 0.06 V. The capacity ratio between the charging stages I and II is 0.1 to 1:1, preferably 0.3 to 0.9:1, and more preferably 0.6 to 0.8:1.

[0024] The present invention also provides a method for producing a method for manufacturing a semiconductor device comprising the steps of: a step A of mixing a mixed solution of a nickel source compound and a manganese source compound, a solution of a crystal grain refiner, a complexing agent, and a precipitating agent, and carrying out a coprecipitation reaction to obtain a suspension I; a step B of mixing a mixed solution of a nickel source compound and a manganese source compound, a complexing agent, a precipitant, and the suspension I, and carrying out a coprecipitation reaction to obtain a suspension II; A step C of filtering, washing and drying the suspension II to obtain a lithium nickel manganese oxide precursor; and D. mixing the lithium nickel manganese oxide precursor with a lithium source compound and sintering the mixture to obtain a high-voltage lithium nickel manganese oxide-based positive electrode material.

[0025] In the present invention, first, a mixed solution of a nickel source compound and a manganese source compound, and a solution of a grain refiner are prepared, respectively.

[0026] Here, in the mixed solution of the nickel source compound and the manganese source compound, the molar ratio of nickel to manganese is 1:3. The nickel source compound is selected from the group consisting of nickel sulfate, nickel nitrate, nickel chloride, and combinations thereof. The manganese source compound is manganese sulfate and / or manganese chloride.

[0027] In the grain refiner solution, the grain refiner is selected from the group consisting of niobium chloride, ammonium niobium oxalate, niobium fluoride, potassium hexafluoroniobate, molybdenum chloride, sodium molybdate, molybdenum oxalate, molybdenum fluoride, molybdenum sulfide dihydrate, and combinations thereof, preferably selected from the group consisting of niobium chloride, niobium fluoride, molybdenum chloride, molybdenum fluoride, molybdenum sulfide dihydrate, and combinations thereof.

[0028] In the present invention, the molar ratio of the metal ions to the grain refiner in the mixed solution of the nickel source compound and the manganese source compound is 1:0.001-0.05, and more preferably 1:0.002-0.02.

[0029] In the present invention, a mixed solution of a nickel source compound and a manganese source compound, a solution of a crystal grain refining agent, a complexing agent and a precipitating agent are mixed together and subjected to a coprecipitation reaction to obtain suspension I.

[0030] Here, the complexing agent is aqueous ammonia, the precipitating agent is a sodium hydroxide solution, and the maturation time of the coprecipitation reaction is 1 to 12 hours, preferably 2 to 10 hours, and more preferably 4 to 8 hours.

[0031] After the coprecipitation reaction is completed, the mixed solution of the nickel source compound and the manganese source compound, the complexing agent, the precipitating agent and the suspension I are mixed together to carry out the coprecipitation reaction, thereby obtaining suspension II.

[0032] Here, in the mixed solution of the nickel source compound and the manganese source compound, the molar ratio of nickel to manganese is 1:2.5 to 3.5, preferably 1:3. The nickel source compound is selected from the group consisting of nickel sulfate, nickel nitrate, nickel chloride, and combinations thereof. The manganese source compound is manganese sulfate and / or manganese chloride. The complexing agent is ammonia water. The precipitating agent is a sodium hydroxide solution.

[0033] The maturation time for the coprecipitation reaction is 2 to 24 hours, preferably 4 to 20 hours, and more preferably 6 to 18 hours.

[0034] The molar ratio of the amount of the mixed solution of the nickel source compound and the manganese source compound in step A) to the amount of the mixed solution of the nickel source compound and the manganese source compound in step B) is 0.1 to 1:1, preferably 0.2 to 0.6:1, and more preferably 0.3 to 0.5:1.

[0035] After obtaining the suspension II, the suspension II is filtered, washed, and dried to obtain the lithium nickel manganese oxide precursor. In the present invention, the filtering, washing, and drying methods are not particularly limited, and may be any methods known to those skilled in the art.

[0036] Finally, the lithium nickel manganese oxide precursor is mixed with a lithium source compound and sintered to obtain a high voltage lithium nickel manganese oxide based positive electrode material.

[0037] wherein the lithium source compound is selected from the group consisting of lithium carbonate, lithium hydroxide, lithium chloride, lithium fluoride, and combinations thereof. The molar ratio of the lithium source compound to the lithium nickel manganate precursor is 1 to 1.1:2, preferably 1.02 to 1.08:2, and more preferably 1.04 to 1.06:2.

[0038] The sintering is carried out at a temperature of 750 to 950° C., preferably 800 to 900° C., for 6 to 24 hours, preferably 8 to 20 hours, and more preferably 10 to 18 hours.

[0039] The present invention also provides a lithium ion battery comprising the high voltage lithium nickel manganese oxide-based positive electrode material. The positive electrode material provided by the present invention has a shell-core structure in which the surface layer is made of large primary particles and the interior is made of small primary particles. Due to the large particle high density structure of the surface layer, the lithium nickel manganese oxide positive electrode material is not crushed after roll pressing, and the dissolution of manganese due to the infiltration of electrolyte into the material can be effectively avoided, thus improving the pressing performance and cycle performance of the material. In addition, the small particle structure in the interior increases the lithium ion mobility and electrical conductivity, improving the rate performance of the material. In addition, the manufacturing method of the positive electrode material provided by the present invention is a simple and controllable process, environmentally friendly, advantageous for rapid and large-scale production, and has low production costs. EXAMPLES

[0040] In order to further clarify the present invention, the high voltage lithium nickel manganese oxide-based positive electrode material provided by the present invention and its preparation method and application are described below in conjunction with examples, but the scope of protection of the present invention is not limited by the following examples.

[0041] Example 1 S1: A 2 mol / L mixed solution of nickel sulfate and manganese sulfate was prepared with a molar ratio of metal ions of 1:3. A 0.2 mol / L sodium molybdate solution, a 0.2 mol / L aqueous ammonia solution, and a 4 mol / L sodium hydroxide solution were also prepared.

[0042] S2: The obtained mixed solution and sodium molybdate solution were mixed uniformly with a molar ratio of nickel manganese ions and molybdenum ions of 1:0.002, and added to a reaction vessel together with an aqueous ammonia solution and a sodium hydroxide solution to carry out a coprecipitation reaction. After aging for 2 hours, suspension I was obtained.

[0043] S3: The obtained mixed solution, aqueous ammonia solution, and sodium hydroxide solution were added to suspension I, and a coprecipitation reaction was carried out. After aging for 12 hours, suspension II was obtained. Here, the concentrations of the mixed solution, aqueous ammonia solution, and sodium hydroxide solution were the same as those in step S1, and the molar ratio of the mixed solution in step S1 to the mixed solution in step S3 was 0.45:1.

[0044] S4: Suspension II was washed, filtered and dried to obtain lithium nickel manganese oxide precursor.

[0045] S5: Lithium carbonate and the obtained lithium nickel manganese oxide precursor were mixed in a molar ratio of 1:2, and sintered at 830° C. for 6 hours to obtain a high-voltage lithium nickel manganese oxide-based positive electrode material according to the present invention.

[0046] FIG. 1 is an SEM image of the lithium nickel manganese oxide produced in Example 1. FIG. 2 is an SEM image of the cross section of the lithium nickel manganese oxide produced in Example 1. FIG. 3 is an SEM image of the cross section of the lithium nickel manganese oxide produced in Comparative Example 1. As can be seen from FIG. 1, the lithium nickel manganese oxide produced in Example 1 had a particle size of 3 to 5 μm of the large particles in the surface layer. As can be seen from FIG. 2, the lithium nickel manganese oxide produced in Example 1 has a shell-core structure formed of a surface layer made of large particles and an interior made of small particles, the particle size of the small particles in the interior was 200 to 500 nm, the particle size of the positive electrode material was 18.3 ± 1 μm, the core size was 11.2 ± 2 μm, and the thickness of the surface layer was 4.0 ± 1 μm. As can be seen from FIG. 3, the lithium nickel manganese oxide produced in Comparative Example 1 does not have a shell-core structure, and the particle size of the surface and the interior is almost the same at 0.2 to 1 μm.

[0047] A lithium ion battery was fabricated as follows using the positive electrode materials obtained in Example 1 and Comparative Example 1. 9 g of the positive electrode material, 0.5 g of acetylene black, and a polyvinylidene fluoride solution with a solid content of 5% were mixed at room temperature and normal pressure to form a slurry, which was then uniformly applied to the surface of an aluminum foil to obtain a pole piece.

[0048] The pole pieces obtained in the previous step were dried at 80°C and pressed into a compact with an area of ​​1.32 cm 2 The positive electrode was made of a circular sheet of pure lithium, and the negative electrode was made of 1 mol / L LiPF 6 An ethylene carbonate (EC) and dimethyl carbonate (DMC) solution (where the volume ratio of EC to DMC was 1:1) was used as the electrolyte, and a lithium-ion battery was then assembled in a glove box filled with argon gas.

[0049] The results of testing the cycle performance of the manufactured lithium ion battery are shown in Figure 4. Figure 4 is a comparison diagram of the charging curves of the batteries manufactured in Example 1 and Comparative Example 1. As can be seen from Figure 4, the battery manufactured in Example 1 has two obvious charging stages, a charging stage I of 4.71V and a charging stage II of 4.76V, the voltage difference between charging stages I and II is 0.05V, and the capacity ratio between charging stages I and II is 0.8, while the battery manufactured in Comparative Example 1 has one obvious charging stage, the charging stage being 4.75V.

[0050] 5 is a comparative diagram of the rate and cycle performance of the batteries prepared in Example 1 and Comparative Example 1. As can be seen from FIG. 5, the battery prepared in Example 1 had a 0.2C discharge specific capacity of 142.2mAh / g, a 1C discharge specific capacity of 139.1mAh / g, a 2C discharge specific capacity of 134.1mAh / g, a 3C discharge specific capacity of 122.6mAh / g, a 5C discharge specific capacity of 113.0mAh / g, a 5C / 0.2C ratio of 79.5%, and a capacity retention rate of 99.5% after 50 cycles at 1C. In contrast, the battery produced in Comparative Example 1 had a 0.2C discharge specific capacity of 138.3mAh / g, a 1C discharge specific capacity of 130.5mAh / g, a 2C discharge specific capacity of 121.6mAh / g, a 3C discharge specific capacity of 98.9mAh / g, a 5C discharge specific capacity of 85.0mAh / g, a 3C / 0.2C ratio of 61.4%, and a capacity retention rate of 50 cycles at 1C of 91.3%. Thus, the battery of Example 1 was superior to the battery of Comparative Example 1 in both cycle performance and rate performance.

[0051] Table 1 is a comparison table of the compacted densities of Examples 1 to 10 and Comparative Example 1. As can be seen from Table 1, Examples 1 to 10 were clearly superior to Comparative Example 1 in terms of compacted densities. [Table 1]

[0052] Example 2 S1: A 3 mol / L mixed solution of nickel sulfate and manganese sulfate was prepared with a molar ratio of metal ions of 1:3. A 0.5 mol / L molybdenum chloride solution, a 0.5 mol / L aqueous ammonia solution, and a 5 mol / L sodium hydroxide solution were also prepared.

[0053] S2: The obtained mixed solution and molybdenum chloride solution were mixed uniformly with a molar ratio of nickel manganese ions and molybdenum ions of 1:0.001, and added to a reaction vessel together with an aqueous ammonia solution and a sodium hydroxide solution to carry out a coprecipitation reaction. After aging for 1 hour, suspension I was obtained.

[0054] S3: The obtained mixed solution, aqueous ammonia solution, and sodium hydroxide solution were added to suspension I, and a coprecipitation reaction was carried out. After aging for 6 hours, suspension II was obtained. Here, the concentrations of the mixed solution, aqueous ammonia solution, and sodium hydroxide solution were the same as those in step S1, and the molar ratio of the mixed solution in step S1 to the mixed solution in step S3 was 0.4:1.

[0055] S4: Suspension II was washed, filtered and dried to obtain lithium nickel manganese oxide precursor.

[0056] S5: Lithium carbonate and the obtained lithium nickel manganese oxide precursor were mixed in a molar ratio of 1.02:2, and sintered at 850° C. for 12 hours to obtain a high-voltage lithium nickel manganese oxide-based positive electrode material according to the present invention.

[0057] Example 3 S1: A 2.5 mol / L mixed solution of nickel sulfate and manganese sulfate was prepared with a molar ratio of metal ions of 1:3.1. A 0.4 mol / L niobium chloride solution, a 0.5 mol / L aqueous ammonia solution, and a 5 mol / L sodium hydroxide solution were also prepared.

[0058] S2: The obtained mixed solution and niobium chloride solution were mixed uniformly with a molar ratio of nickel manganese ions and niobium ions of 1:0.01, and added to a reaction vessel together with an aqueous ammonia solution and a sodium hydroxide solution to carry out a coprecipitation reaction. After aging for 5 hours, suspension I was obtained.

[0059] S3: The obtained mixed solution, aqueous ammonia solution, and sodium hydroxide solution were added to suspension I, and a coprecipitation reaction was carried out. After aging for 24 hours, suspension II was obtained. Here, the concentrations of the mixed solution, aqueous ammonia solution, and sodium hydroxide solution were the same as those in step S1, and the molar ratio of the mixed solution in step S1 to the mixed solution in step S3 was 0.5:1.

[0060] S4: Suspension II was washed, filtered and dried to obtain lithium nickel manganese oxide precursor.

[0061] S5: Lithium carbonate and the obtained lithium nickel manganese oxide precursor were mixed in a molar ratio of 1.01:2, and sintered at 870° C. for 12 hours to obtain a high-voltage lithium nickel manganese oxide-based positive electrode material according to the present invention.

[0062] Example 4 S1: A 2.5 mol / L mixed solution of nickel sulfate and manganese sulfate was prepared with a molar ratio of metal ions of 1:2.95. A 0.1 mol / L niobium fluoride solution, a 2.5 mol / L aqueous ammonia solution, and a 2.5 mol / L sodium hydroxide solution were also prepared.

[0063] S2: The obtained mixed solution and niobium fluoride solution were mixed uniformly with a molar ratio of nickel manganese ions and niobium ions of 1:0.005, and added to a reaction vessel together with an aqueous ammonia solution and a sodium hydroxide solution to carry out a coprecipitation reaction. After aging for 3 hours, suspension I was obtained.

[0064] S3: The obtained mixed solution, aqueous ammonia solution, and sodium hydroxide solution were added to suspension I, and a coprecipitation reaction was carried out. After aging for 20 hours, suspension II was obtained. Here, the concentrations of the mixed solution, aqueous ammonia solution, and sodium hydroxide solution were the same as those in step S1, and the molar ratio of the mixed solution in step S1 to the mixed solution in step S3 was 0.6:1.

[0065] S4: Suspension II was washed, filtered and dried to obtain lithium nickel manganese oxide precursor.

[0066] S5: Lithium carbonate and the obtained lithium nickel manganese oxide precursor were mixed in a molar ratio of 1:2, and sintered at 950° C. for 8 hours to obtain a high-voltage lithium nickel manganese oxide-based positive electrode material according to the present invention.

[0067] Example 5 S1: A 2 mol / L mixed solution of nickel sulfate and manganese sulfate was prepared with a molar ratio of metal ions of 1:3.2. A 0.1 mol / L molybdenum sulfide dihydrate solution, a 0.5 mol / L aqueous ammonia solution, and a 5 mol / L sodium hydroxide solution were also prepared.

[0068] S2: The obtained mixed solution and molybdenum sulfide dihydrate solution were mixed uniformly with a molar ratio of nickel manganese ions and molybdenum ions of 1:0.02, and added to a reaction vessel together with an aqueous ammonia solution and a sodium hydroxide solution to carry out a coprecipitation reaction. After aging for 6 hours, suspension I was obtained.

[0069] S3: The obtained mixed solution, aqueous ammonia solution, and sodium hydroxide solution were added to suspension I, and a coprecipitation reaction was carried out. After aging for 18 hours, suspension II was obtained. Here, the concentrations of the mixed solution, aqueous ammonia solution, and sodium hydroxide solution were the same as those in step S1, and the molar ratio of the mixed solution in step S1 to the mixed solution in step S3 was 0.9:1.

[0070] S4: Suspension II was washed, filtered and dried to obtain lithium nickel manganese oxide precursor.

[0071] S5: Lithium carbonate and the obtained lithium nickel manganese oxide precursor were mixed in a molar ratio of 1.05:2, and sintered at 780° C. for 20 hours to obtain a high-voltage lithium nickel manganese oxide-based positive electrode material according to the present invention.

[0072] Example 6 S1: A 4 mol / L mixed solution of nickel sulfate and manganese sulfate was prepared with a molar ratio of metal ions of 1:3. A 0.5 mol / L molybdenum oxalate solution, a 1 mol / L aqueous ammonia solution, and a 4 mol / L sodium hydroxide solution were also prepared.

[0073] S2: The obtained mixed solution and molybdenum oxalate solution were mixed uniformly with a molar ratio of nickel manganese ions and molybdenum ions of 1:0.003, and added to a reaction vessel together with an aqueous ammonia solution and a sodium hydroxide solution to carry out a coprecipitation reaction. After aging for 2 hours, suspension I was obtained.

[0074] S3: The obtained mixed solution, aqueous ammonia solution, and sodium hydroxide solution were added to suspension I, and a coprecipitation reaction was carried out. After aging for 12 hours, suspension II was obtained. Here, the concentrations of the mixed solution, aqueous ammonia solution, and sodium hydroxide solution were the same as those in step S1, and the molar ratio of the mixed solution in step S1 to the mixed solution in step S3 was 0.42:1.

[0075] S4: Suspension II was washed, filtered and dried to obtain lithium nickel manganese oxide precursor.

[0076] S5: Lithium carbonate and the obtained lithium nickel manganese oxide precursor were mixed in a molar ratio of 1.06:2, and sintered at 920°C for 18 hours to obtain a high-voltage lithium nickel manganese oxide-based positive electrode material according to the present invention.

[0077] Example 7 S1: A 2 mol / L mixed solution of nickel sulfate and manganese sulfate was prepared with a molar ratio of metal ions of 1:3.5. A 0.6 mol / L niobium chloride solution, a 0.3 mol / L aqueous ammonia solution, and a 5 mol / L sodium hydroxide solution were also prepared.

[0078] S2: The obtained mixed solution and niobium chloride solution were mixed uniformly with a molar ratio of nickel manganese ions and niobium ions of 1:0.005, and added to a reaction vessel together with an aqueous ammonia solution and a sodium hydroxide solution to carry out a coprecipitation reaction. After aging for 1 hour, suspension I was obtained.

[0079] S3: The obtained mixed solution, aqueous ammonia solution, and sodium hydroxide solution were added to suspension I, and a coprecipitation reaction was carried out. After aging for 8 hours, suspension II was obtained. Here, the concentrations of the mixed solution, aqueous ammonia solution, and sodium hydroxide solution were the same as those in step S1, and the molar ratio of the mixed solution in step S1 to the mixed solution in step S3 was 0.55:1.

[0080] S4: Suspension II was washed, filtered and dried to obtain lithium nickel manganese oxide precursor.

[0081] S5: Lithium carbonate and the obtained lithium nickel manganese oxide precursor were mixed in a molar ratio of 1.05:2, and sintered at 900° C. for 15 hours to obtain a high-voltage lithium nickel manganese oxide-based positive electrode material according to the present invention.

[0082] Example 8 S1: A 2 mol / L mixed solution of nickel sulfate and manganese sulfate was prepared with a molar ratio of metal ions of 1:2.8. A 0.8 mol / L sodium molybdate solution, a 2.5 mol / L aqueous ammonia solution, and a 2.5 mol / L sodium hydroxide solution were also prepared.

[0083] S2: The obtained mixed solution and sodium molybdate solution were mixed uniformly with a molar ratio of nickel manganese ions and molybdenum ions of 1:0.015, and added to a reaction vessel together with an aqueous ammonia solution and a sodium hydroxide solution to carry out a coprecipitation reaction. After aging for 6 hours, suspension I was obtained.

[0084] S3: The obtained mixed solution, aqueous ammonia solution, and sodium hydroxide solution were added to suspension I, and a coprecipitation reaction was carried out. After aging for 16 hours, suspension II was obtained. Here, the concentrations of the mixed solution, aqueous ammonia solution, and sodium hydroxide solution were the same as those in step S1, and the molar ratio of the mixed solution in step S1 to the mixed solution in step S3 was 1:1.

[0085] S4: Suspension II was washed, filtered and dried to obtain lithium nickel manganese oxide precursor.

[0086] S5: Lithium carbonate and the obtained lithium nickel manganese oxide precursor were mixed in a molar ratio of 1:2, and sintered at 760°C for 16 hours to obtain a high-voltage lithium nickel manganese oxide-based positive electrode material according to the present invention.

[0087] Example 9 S1: A 2 mol / L mixed solution of nickel sulfate and manganese sulfate was prepared with a molar ratio of metal ions of 1:3.02, and a 0.2 mol / L potassium hexafluoroniobate solution, a 0.25 mol / L aqueous ammonia solution, and a 5 mol / L sodium hydroxide solution were also prepared.

[0088] S2: The obtained mixed solution and potassium hexafluoroniobate solution were mixed uniformly with a molar ratio of nickel manganese ions and niobium ions of 1:0.004, and added to a reaction vessel together with an aqueous ammonia solution and a sodium hydroxide solution to carry out a coprecipitation reaction. After aging for 2 hours, suspension I was obtained.

[0089] S3: The obtained mixed solution, aqueous ammonia solution, and sodium hydroxide solution were added to suspension I, and a coprecipitation reaction was carried out. After aging for 8 hours, suspension II was obtained. Here, the concentrations of the mixed solution, aqueous ammonia solution, and sodium hydroxide solution were the same as those in step S1, and the molar ratio of the mixed solution in step S1 to the mixed solution in step S3 was 0.35:1.

[0090] S4: Suspension II was washed, filtered and dried to obtain lithium nickel manganese oxide precursor.

[0091] S5: Lithium carbonate and the obtained lithium nickel manganese oxide precursor were mixed in a molar ratio of 1.06:2, and sintered at 830° C. for 12 hours to obtain a high-voltage lithium nickel manganese oxide-based positive electrode material according to the present invention.

[0092] Example 10 S1: A 2 mol / L mixed solution of nickel sulfate and manganese sulfate was prepared with a molar ratio of metal ions of 1:2.98, and a 0.35 mol / L molybdenum fluoride solution, a 0.5 mol / L aqueous ammonia solution, and a 5 mol / L sodium hydroxide solution were also prepared.

[0093] S2: The obtained mixed solution and molybdenum fluoride solution were mixed uniformly with a molar ratio of nickel manganese ions and molybdenum ions of 1:0.04, and added to a reaction vessel together with an aqueous ammonia solution and a sodium hydroxide solution to carry out a coprecipitation reaction. After aging for 12 hours, suspension I was obtained.

[0094] S3: The obtained mixed solution, aqueous ammonia solution, and sodium hydroxide solution were added to suspension I, and a coprecipitation reaction was carried out. After aging for 24 hours, suspension II was obtained. Here, the concentrations of the mixed solution, aqueous ammonia solution, and sodium hydroxide solution were the same as those in step S1, and the molar ratio of the mixed solution in step S1 to the mixed solution in step S3 was 0.1:1.

[0095] S4: Suspension II was washed, filtered and dried to obtain lithium nickel manganese oxide precursor.

[0096] S5: Lithium carbonate and the obtained lithium nickel manganese oxide precursor were mixed in a molar ratio of 1:2, and sintered at 860° C. for 10 hours to obtain a high-voltage lithium nickel manganese oxide-based positive electrode material according to the present invention.

[0097] Comparative Example 1 S1: A 2 mol / L mixed solution of nickel sulfate and manganese sulfate was prepared with a molar ratio of metal ions of 1:3, and a 0.2 mol / L aqueous ammonia solution and a 4 mol / L sodium hydroxide solution were prepared.

[0098] S2: The obtained mixed solution was added to a reactor together with an aqueous ammonia solution and a sodium hydroxide solution, and a coprecipitation reaction was carried out. After aging, a suspension was obtained.

[0099] S4: The suspension was washed, filtered and dried to obtain the lithium nickel manganese oxide precursor.

[0100] S5: Lithium carbonate and the obtained lithium nickel manganese oxide precursor were mixed in a molar ratio of 1:2, and sintered at 830° C. for 16 hours to obtain a high-voltage lithium nickel manganese oxide-based positive electrode material according to the present invention.

[0101] It should be noted that the above description is merely a preferred embodiment of the present invention, and those skilled in the art may make some improvements and modifications without departing from the principles of the present invention, and these improvements and modifications are also deemed to be included in the protection scope of the present invention.

Claims

1. A high-voltage lithium nickel manganese oxide-based positive electrode material, characterized in that it has a core-shell structure formed of a core made of small primary particles having a particle size of 50 to 800 nm and a surface layer made of large primary particles having a particle size of 1 to 5 μm.

2. 2. The positive electrode material according to claim 1, wherein the positive electrode material has a particle size of 6 to 15 μm, a core size of 1 to 10 μm, and a surface layer thickness of 3 to 5 μm.

3. The cathode material has two charging stages, a charging stage I in the range of 4.6 to 4.74 V and a charging stage II in the range of 4.74 to 4.8 V, the voltage difference between the charging stage I and the charging stage II is 0.02 to 0.2 V, and the capacity ratio between the charging stage I and the charging stage II is 0.1 to 1:

1. The cathode material according to claim 1.

4. A method for producing a high-voltage lithium nickel manganese oxide-based positive electrode material according to any one of claims 1 to 3, a step A of mixing a mixed solution of a nickel source compound and a manganese source compound, a solution of a crystal grain refiner, a complexing agent, and a precipitating agent, and carrying out a coprecipitation reaction to obtain a suspension I; a step B of mixing a mixed solution of a nickel source compound and a manganese source compound, a complexing agent, a precipitant, and the suspension I, and carrying out a coprecipitation reaction to obtain a suspension II; Step C of filtering, washing and drying the suspension II to obtain a lithium nickel manganese oxide precursor; and D. mixing the lithium nickel manganese oxide precursor with a lithium source compound and sintering the mixture to obtain a high-voltage lithium nickel manganese oxide-based positive electrode material.

5. the nickel source compound is selected from the group consisting of nickel sulfate, nickel nitrate, nickel chloride, and combinations thereof; the manganese source compound is manganese sulfate or / and manganese chloride; the complexing agent is aqueous ammonia, 5. The process according to claim 4, wherein the precipitating agent is a sodium hydroxide solution.

6. 5. The process of claim 4, wherein the grain refiner is selected from the group consisting of niobium chloride, ammonium niobium oxalate, niobium fluoride, potassium hexafluoroniobate, molybdenum chloride, sodium molybdate, molybdenum oxalate, molybdenum fluoride, molybdenum sulfide dihydrate, and combinations thereof.

7. The method according to claim 4, wherein in step A), a molar ratio of metal ions in the mixed solution of the nickel source compound and the manganese source compound to the grain refiner is 1:0.001-0.

05.

8. 5. The method according to claim 4, wherein a molar ratio of amounts of the mixed solution of the nickel source compound and the manganese source compound in step A) to the mixed solution of the nickel source compound and the manganese source compound in step B) is 0.1 to 1:

1.

9. In step D), the lithium source compound is selected from the group consisting of lithium carbonate, lithium hydroxide, lithium chloride, lithium fluoride, and combinations thereof; The method according to claim 4, wherein the sintering is carried out at a temperature of 750 to 950° C. for 6 to 24 hours.

10. A lithium-ion battery comprising the high-voltage lithium nickel manganese oxide-based positive electrode material according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Lithium manganese iron phosphate-based composite positive electrode material and preparation method thereof

    CN108598386A

  • Nickel-containing precursor, nickel-containing composite material, and preparation methods and applications of nickel-containing precursor and nickel-containing composite material

    CN112624208A

  • Lithium ion battery oxide positive electrode material and preparation method thereof

    CN113437264A

  • Nickel compound hydroxide and method for producing the same, positive pole active substance for nonaqueous electrolyte secondary cell and method for producing the same, and nonaqueous electrolyte secondary cell

    JP2013147416A

  • Positive electrode active material for secondary battery, manufacturing method thereof, and secondary battery including the same

    JP2018506156A